Checking In: A Pilot of a PhysicianDelivered Intervention to Increase Parent–Adolescent Communication About Blood Glucose Monitoring. (December 2015) - Monaghan, Maureen; Clary, Lauren; Mehta, Priya; Stern, Alexa; Sharkey, Christina; Cogen, Fran R.; Vaidyanathan, Priya; Streisand, Randi
Low-cost, translatable interventions to promote adherence in adolescents with type 1 diabetes are needed. This study evaluated a brief physician-delivered intervention designed to increase parent–adolescent communication about blood glucose monitoring. Thirty adolescent–parent dyads completed baseline questionnaires and received the physician-delivered intervention. Participants completed follow-up questionnaires at 12 weeks; HbA1c and glucometer data were abstracted from medical charts. Parent-reported conflict surrounding diabetes management decreased from pre- to postintervention. Participants who reported adhering to the intervention plan (n = 15) demonstrated an increase in blood glucose monitoring frequency and trends in improved HbA1c and parental diabetes collaboration from pre- to postintervention. Participants and physicians reported overall satisfaction with the program. Results demonstrate initial feasibility as well as a trend toward improvement in diabetes-specific health indicators for parent–adolescent dyads who adhered to program components. Frequent joint review of glucometer data can be a useful strategy to improve type 1 diabetes–related health outcomes and parent–adolescent communication.